A radiographic evaluation of temporomandibular and hand (Metacarpophalangeal) / wrist joints of patients with adult rheumatoid arthritis - Seema Kurup; Harshkant Gharote; Renju Jose (Wolters Kluwer Medknow Publications, 2012)
Background: A review of literature revealed that, although the involvement of temporomandibular joint (TMJ) in rheumatoid arthritis (RA) patients is not uncommon, variation in presentation persist. Comparative studies of bony changes in the right and left TMJ with the right and left peripheral hand (Metacarpophalangeal-MCP)/wrist joints have not been done, to the best of our knowledge. Materials and Methods: In this cross-sectional study, the temporomandibular and hand (MCP) and wrist joints of fifteen rheumatoid arthritis patients were evaluated with questionnaires, clinical and lab assessment and radiographically using conventional radiographs and computed tomography. Students t-test was applied for the statistical analysis of the data obtained and a P value of 0.05 was considered as statistically significant. Results: Comparisons between the right TMJ with right MCP/wrist joint and left TMJ with left MCP/wrist joint did not reveal statistically significant results. Radiographically, flattening and erosions were the common manifestations. MCP joints were more affected than the wrist, but whenever the wrist was involved, it was more likely to be bilaterally affected. Conclusions: Although the TMJ showed osseous changes of a higher grade than the hand (MCP) and wrist joints radiographically, it was observed that patients were more aware of the peripheral joint discomfort. There were no significant differences between TMJ and peripheral joints on both right and left sides.